2003
DOI: 10.1046/j.1365-2796.2003.01110.x
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and relation to other risk factors in postmenopausal women with coronary artery disease, with particular reference to whole blood viscosity and β‐cell function

Abstract: Objectives. To investigate possible associations between smoking habits and other coronary risk factors in postmenopausal women with known coronary heart disease (CHD). Setting. The study was conducted at a university clinic. Subjects. A total of 118 postmenopausal women with CHD verified with angiography, consecutively recruited. Interventions. Conventional treatment for CHD. The women were randomized to hormone replacement therapy (HRT) with transdermal 17-b oestradiol and medroxyprogesterone acetate, or to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…Our WBV results share the same range with published data using a similar rotational method at high shear rates (200 -208 s À 1 ) [13,14].…”
Section: Discussionsupporting
confidence: 90%
“…Our WBV results share the same range with published data using a similar rotational method at high shear rates (200 -208 s À 1 ) [13,14].…”
Section: Discussionsupporting
confidence: 90%
“…Increased blood viscosity at the date of admission may have been mediated by dehydration because patients returned 13 to normal hydrated conditions after 2 weeks. The importance of dehydration needs to be emphasized in the pathogenesis of SAO.…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10] Furthermore, relationships have been reported between blood viscosity and some cardiovascular risk factors, such as hypertension, dyslipidemia, smoking, and obesity. [11][12][13][14] An increase in blood viscosity has been identified in the acute phase of ischemic stroke, similar to other thrombotic diseases. [15][16][17][18][19] However, actual 4 measurements of blood viscosity have not been performed because of the stereotypical belief that blood viscosity increases equally in all ischemic stroke subtypes, which is within expectations and with less clinical value.…”
Section: Introductionmentioning
confidence: 94%
“…In a largescale prospective study involving 100,000 people, Rimm et al (1993) showed that smoking was an independent risk factor for diabetes, suggesting that one of the physiological actions of smoking on the bodily functions may consist in the suppression of early insulin response (Os et al 2003), in conjunction with the elevation of TG levels in the blood that smoking induces (Freedman et al 1986).…”
Section: Discussionmentioning
confidence: 99%